2015
DOI: 10.1111/hae.12698
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after total knee arthroplasty in haemophilic patients with stiff knees

Abstract: Total knee arthroplasty in haemophilic patients presenting with stiff knees results in significant improvement of function and reduction in pain. Although the clinical outcome is inferior compared to nonstiff knees reported in the literature, joint replacement surgery can be successfully performed in this particular group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0
6

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 29 publications
(41 reference statements)
4
37
0
6
Order By: Relevance
“…(Fig. 3) This can possibly be explained by Heeg et al [28] and Zingg et al [32] having high complication rates, and a postoperative loss in ROM, while Innocenti et al [37] had extensive synovium removal with use of a specific prosthesis and Strauss et al [30] had preoperative ROM 50°or less, indicating a more severe impairment at baseline.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…(Fig. 3) This can possibly be explained by Heeg et al [28] and Zingg et al [32] having high complication rates, and a postoperative loss in ROM, while Innocenti et al [37] had extensive synovium removal with use of a specific prosthesis and Strauss et al [30] had preoperative ROM 50°or less, indicating a more severe impairment at baseline.…”
Section: Discussionmentioning
confidence: 98%
“…2). Heeg et al [28] and Zingg et al [32] reported no change or a decrease in flexion ROM, while Innocenti et al [37] and Strauss et al [30] reported >30°increase in flexion ROM. (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced pain and increased joint movement were reported by patients with severe HA who underwent joint replacement surgery, although this improvement did not change previous functional scores and was based solely on clinical experience. 33 This result is indicated by the high level of subjective satisfaction of the patient with the postoperative results of total knee arthroplasty, even in cases in which the outcomes are poor.…”
Section: Discussionmentioning
confidence: 99%